1994
DOI: 10.1037/0278-7393.20.3.694
|View full text |Cite
|
Sign up to set email alerts
|

Configural and elemental strategies in predictive learning.

Abstract: When 2 cues occur together and reliably predict an outcome, Ss often judge the effect of the compound as reducible to the individual effects of the elements. This elemental processing in predictive learning is perhaps the single most important aspect of most theories of human inference. Surprisingly, selectional processing was not observed in either blocking or conditioned inhibition problems. Only when the learner had past experience with another problem encouraging an elemental strategy were the expected sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
200
2
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(224 citation statements)
references
References 45 publications
18
200
2
1
Order By: Relevance
“…Our results also parallel a feature of associative models of Pavlovian conditioning and causal learning (see Williams & Braker, 1999), in which experience with compound cues-analogous to our multidimensional objects-results in associations involving those compounds, but not their constituent elements (e.g., Pearce, 1987; see also Shanks, Charles, Darby, & Azmi, 1998;Williams, Sagness, & McPhee, 1994).…”
Section: The Units Of Vslsupporting
confidence: 74%
“…Our results also parallel a feature of associative models of Pavlovian conditioning and causal learning (see Williams & Braker, 1999), in which experience with compound cues-analogous to our multidimensional objects-results in associations involving those compounds, but not their constituent elements (e.g., Pearce, 1987; see also Shanks, Charles, Darby, & Azmi, 1998;Williams, Sagness, & McPhee, 1994).…”
Section: The Units Of Vslsupporting
confidence: 74%
“…For example, if A signals event O during initial training, and subsequently O is signaled by the combination of A and B, at a final test B on its own will not reliably elicit a response. Blocking is known to play a powerful role in human contingency judgments (e.g., Williams, Sagness, & McPhee, 1994) and, of greatest interest here, in categorization (e.g., Gluck & Bower, 1988;Shanks, 1991Shanks, , 1993). …”
Section: Prior Knowledge and New Learningmentioning
confidence: 99%
“…For example, studies investigating learning of stimulus-outcome relations in human subjects have shown that performance to an overshadowed stimulus can be retroactively increased by posttraining exposures to the paired stimulus. Specifically, if subjects learn the association between a compound cue, AB, and a particular outcome, then the predictive value accorded A can be retroactively decreased by paired presentations of B and the outcome (Chapman, 1991;Dickinson & Burke, 1996;Shanks, 1985;Van Hamme & Wasserman, 1994;Williams, Sagness, & McPhee, 1994) or retroThe research was supported by a grant from the Australian Research Council, and the experimental procedures were approved by the Animal Care and Ethics Committee (ACEC) of the University of New South Wales, The authors are grateful to P. Lovibond and R. Richardson for comments. Correspondence should be addressed to 1.A.…”
mentioning
confidence: 99%